Transaksi Afiliasi Dan Transaksi Benturan Kepentingan Pada Pasar Modal Di Indonesia - Jr, Muhammad Edwin (Universitas Sang Bumi Ruwa Jurai, 2024)
The discussion of this article is divided into three discussions. First, discuss the meaning of affiliate transactions and conflict of interest transactions. Second, regarding the regulation of information disclosure as a condition for carrying out affiliate transactions and conflict of interest transactions. Then the third discusses administrative sanctions for violators of the provisions on affiliate transactions and conflict of interest transactions. Thus, based on these three discussions, it can be concluded that affiliate transactions and conflict of interest transactions are not things that are prohibited but things that must be regulated so as not to cause losses to independent shareholders